2018
DOI: 10.1093/jjco/hyy013
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate-cysteine ligase catalytic subunit is associated with cisplatin resistance in lung adenocarcinoma

Abstract: High tumor expression levels of glutamate-cysteine ligase catalytic subunit may be a potential predictor of treatment failure in lung adenocarcinoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…The intracellular glutathione pool is regulated by a series of enzymes involved in its synthesis, utilization and recycling, and high expression levels of these genes have been seen to promote cisplatin resistance in lung adenocarcinoma cell lines, with the glutamate cysteine ligase catalytic subunit (GCLC) expression being proposed as a potential predictor of treatment failure 30 . Importantly, the expression of these genes is controlled by the transcription factor NRF2, and several studies have shown that high amounts of NRF2 can induce cisplatin resistance in ovarian, bladder, and head and neck cancers 31–33 .…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular glutathione pool is regulated by a series of enzymes involved in its synthesis, utilization and recycling, and high expression levels of these genes have been seen to promote cisplatin resistance in lung adenocarcinoma cell lines, with the glutamate cysteine ligase catalytic subunit (GCLC) expression being proposed as a potential predictor of treatment failure 30 . Importantly, the expression of these genes is controlled by the transcription factor NRF2, and several studies have shown that high amounts of NRF2 can induce cisplatin resistance in ovarian, bladder, and head and neck cancers 31–33 .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, majority of patients still suffer from the reoccurring LAC [5]. Moreover, cisplatin has been shown to be essential when treating LAC, with its sensitivity to cisplatin being directly associated to the prognosis [6]. In previous studies, by inhibiting contactin-1, the sensitivity levels of LAC increase, thereby affecting the chemotherapeutic efficacy related to cisplatin based regimens among patients suffering from LAC [7].…”
Section: Introductionmentioning
confidence: 99%
“…As well, GCLC has been found to overexpress in liver metastases of colorectal cancer and promotes cancer cell survival ( 47 ). Also, GCLC activation is associated with anti-tumor drug resistance in breast, lung, liver, head, and neck cancer ( 37 , 48 50 ). Based on our in silico results and previous studies, we propose that both ANPEP and GCL have key roles in EMT development, however prognostic significance, as well as its potential as a pharmacological target, requires further in-depth investigations.…”
Section: Discussionmentioning
confidence: 99%